Peripheral Neuropathy in Adolescents and Young Adults With Type 1 and Type 2 Diabetes From the SEARCH for Diabetes in Youth Follow-up Cohort: A pilot study - JAISWAL, Mamta; LAUER, Abigail; RODRIGUEZ, Beatriz L; POP-BUSUI, Rodica; FELDMAN, Eva L; MARTIN, Catherine L; BELL, Ronny A; DIVERS, Jasmin; DABELEA, Dana; PETTITT, David J; SAYDAH, Sharon; PIHOKER, Catherine; et al. (Diabetes care, 2013)
To estimate the prevalence of and risk factors for diabetic peripheral neuropathy (DPN) in a pilot study among youth participating in the SEARCH for Diabetes in Youth study. DPN was assessed using the Michigan Neuropathy Screening Instrument (MNSI) (examination for foot abnormalities, distal vibration perception, and ankle reflexes). An MNSI exam (MNSIE) score >2 is diagnostic for DPN. The MNSIE was completed in 399 subjects, including 329 youth with type 1 diabetes (mean age 15.7 ± 4.3 years, duration 6.2 ± 0.9 years) and 70 with type 2 diabetes (mean age 21.6 ± 4.1 years, duration 7.6 ± 1.8 years). Glycated hemoglobin (A1C) was similar in both groups (8.8 ± 1.8% for type 1 vs. 8.5 ± 2.9% for type 2). The prevalence of DPN was significantly higher in youth with type 2 compared with those with type 1 diabetes (25.7 vs. 8.2%; P < 0.0001). In unadjusted analyses, diabetes type, older age, longer duration of diabetes, increased waist circumference, elevated blood pressure, lower HDL cholesterol, and presence of microalbuminuria (urinary albumin-to-creatinine ratio >30 mg/g) were associated with DPN. The association between diabetes type and DPN remained significant after adjustment for age and sex (odds ratio 2.29 [95% CI 1.05-5.02], P = 0.03). DPN prevalence among youth with type 2 diabetes approached rates reported in adult populations with diabetes. Our findings suggest not only that youth with diabetes are at risk for DPN but also that many already show measurable signs of DPN.